Penyusunan Data Dasar Masyarakat sebagai Upaya Pembaharuan Data di Desa Wolosambi Kecamatan Lio Timur Kabupaten Ende - Yohanes Paulus Luciany (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2022)
Development in rural areas has become a concern of the central government where in the last decade, the government has disbursed large funds for each village. This village fund is used for development in the village. For this purpose, the validity of village data is very important for the process of analysis and preparation of programs for village development. The priority of development in the village is the spearhead of public services in Indonesia, where the village is in direct contact with the community. The purpose of this activity is to compile basic community data as an effort to update data in Wolosambi Village, East Lio District, Ende Regency. The activity of compiling the basic data profile of the population of Wolosambi Village, Lio Timur District, Ende Regency was carried out through several stages, namely coordination, data collection, data compilation, data processing, preparation of village basic data profile and product delivery. Based on the results of observations and analysis, a Wolosambi Village Profile is produced which includes a general description of the Wolosambi village profile.